Exploring ICT Integration in Hausa Language Instruction: A Case Study at Jigawa State College of Education and Legal Studies, Ringim (British Journal of Multidisciplinary and Advanced Studies, 2024)
This research examines the transformative impact of integrated Information and Communication Technology (ICT) in Hausa language instruction at Jigawa State College of Education and Legal Studies, Ringim. The study evaluates the current status of ICT integration in teaching Hausa language, gauges the perspectives of pre-service teachers on the efficacy of ICT tools in enhancing language proficiency, identifies challenges and opportunities tied to ICT incorporation, and proposes innovative strategies and best practices for optimizing technology use in language education. Employing a multifaceted research methodology, including surveys, interviews, and observations, this investigation provides a nuanced understanding of the intricate relationship between ICT integration and Hausa language instruction specific to the context of Jigawa State College of Education and Legal Studies, Ringim. The findings offer valuable insights and recommendations aligned with best practices for pre-service teachers, contributing to the advancement of language education practices within the institution.